The Phenomenology of the “Sitting Inside”: A Socio-Philosophical Analysis - Tetenkov, Nikolay (Տիգրան Մեծ)
The article deals with the problem of transforming human subjectivity. Factors which condition the formation of the internal concept of the Self, as a phenomenon “sitting in-side,” are defined. Aspects connected with the concept of “norm” and “pathology” from positions of modern philoso-phy, social psychology, psychoanalysis and medicine are ana-lyzed. The relevance of the study: at present, there is a radical revision of ideas about the inner component of the self-concept.The aim of the study is to explore the socio-philosophical aspects of multiple subjectivities of the individual from the perspective of the phenomenon of “sitting inside”. In addition to the general scientific methods of analysis and synthesis, the research methodology involves the applica-tion of methods such as the systematic method, the method of interdisciplinary research and the method of hypothetical modelling.The author‟s interpretation of the phenomenon of “multi-ple subjectivities” is given. The results of the study have been the subject of numerous discourses at scientific and practical conferences at international and all-Russian levels and semi-nars.The study concludes that the phenomenon of “sitting in-side” should be characterized as a pathological deformation of personality subjectivity.
Keywords: Social philosophy